Palmitic acid induces autophagy in hepatocytes via JNK2 activation - Tu Qian-qian; Zheng Rui-ying; Li Juan; Hu Liang; Chang Yan-xin; Li Liang; Li Min-hong; Wang Ruo-yu; Huang Dan-dan; Wu Meng-chao; Hu He-ping; Chen Lei; et al. (Acta Pharmacologica Sinica, 2016)
Qian-qian TU1, #, Rui-ying ZHENG2, #, Juan LI3, #, Liang HU1, 4, Yan-xin CHANG1, Liang LI1, Min-hong LI5, Ruo-yu WANG5, Dan-dan HUANG1, Meng-chao WU5, He-ping HU5, *, Lei CHEN1, 6, *, Hong-yang WANG1, 6 1International Co-operation Laboratory on Signal Transduction, Eastern Hepatobiliary Surgery Institute, Second Military Medical University, Shanghai 200433, China; 2Department of Infectious Diseases, Changhai Hospital, Second Military Medical University, Shanghai 200433, China; 3Department of Nutrition and Endocrinology, Changhai Hospital, Second Military Medical University, Shanghai 200433, China; 4Anal-Colorectal Surgery Institute, No 150 Central Hospital of PLA, Luoyang 471031, China; 5Eastern Hepatobiliary Surgery Hospital, Shanghai 200433, China; 6National Center for Liver Cancer, Shanghai 201805, China Aim: Free fatty acid-induced lipotoxicity plays a crucial role in the progression of nonalcoholic fatty liver disease (NAFLD). In the present study we investigated the effects of a high-fat diet and free fatty acids on the autophagic process in hepatocytes in vivo and in vitro and the underlying mechanisms. Methods: LC3-II expression, a hallmark of autophagic flux, was detected in liver specimens from patients with non-alcoholic steatohepatitis (NASH) as well as in the livers of C57BL/6 mice fed a high-fat diet (HFD) up to 16 weeks. LC3-II expression was also analyzed in human SMMC-7721 and HepG2 hepatoma cells exposed to palmitic acid (PA), a saturated fatty acid. PA-induced apoptosis was detected by Annexin V staining and specific cleavage of PARP in the presence and absence of different agents. Results: LC3-II expression was markedly increased in human NASH and in liver tissues of HFD-fed mice. Treatment of SMMC-7721 cells with PA increased LC3-II expression in time- and dose-dependent manners, whereas the unsaturated fatty acid oleic acid had no effect. Inhibition of autophagy with 3MA sensitized SMMC-7721 cells to PA-induced apoptosis, whereas activation of autophagy by rapamycin attenuated PA-induced PARP cleavage. The autophagy-associated proteins Beclin1 and Atg5 were essential for PA-induced autophagy in SMMC-7721 cells. Moreover, pretreatment with SP600125, an inhibitor of JNK, effectively abrogated PA-mediated autophagy and apoptosis. Specific knockdown of JNK2, but not JNK1, in SMMC-7721 cells significantly suppressed PA-induced autophagy and enhanced its pro-apoptotic activity; whereas specific knockdown of JNK1 had the converse effect. Similar results were obtained when HepG2 cells were tested. Conclusion: JNK1 promotes PA-induced lipoapoptosis, whereas JNK2 activates pro-survival autophagy and inhibits PA lipotoxicity. Our results suggest that modulation of autophagy may have therapeutic benefits in the treatment of lipid-related metabolic diseases. Keywords: hepatocytes; nonalcoholic fatty liver disease; free fatty acid; autophagy; apoptosis; palmitic acid; 3MA; rapamycin; SP600125; Beclin1; Atg5; JNK2 We thank Prof Mu-jun ZHAO for providing the GFP-LC3 plasmid. We are grateful to Dong-ping HU, Dan CAO, Dan-dan HUANG and Kun WU for their technical assistance. And we also thank Shanghai Dida Biotechnology Co, Ltd for technical assistance and data analysis. This research was supported by the projects from the Key Program of National Natural Science Foundation of China (90713032 and 81272212). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail chenlei@smmu.edu.cn (Lei CHEN); hp-hu@medmail.com.cn (He-ping HU) Received 2013-06-25 Accepted 2013-10-18